Realizing the Effectiveness of Districts Administration at the Government of Pandeglang Regency, Banten Province, Indonesia - Nugroho, Arif (JPAS (Journal of Public Administration Studies), 2019)
This article discusses the fulfilment of the necessary condition of institutional elements in the District of Pandeglang. Especially in carrying out its capacity as an autonomous region as well as the administrative region of the province. The purpose of this article is to provide a recommendation model in delegating the authority of the Regent to the Head of District based on empirical conditions. This study uses a qualitative approach. The results showed that in Pandeglang District, the fulfilment of the necessary condition of the district institutions such as human resources and the budget was not directly proportional to the legal authority delegated by the Regent. In addition, in the aspect of the legal authority of the Head of District is still not accommodating enough on several aspects including legislation changes, regional characteristics, the spirit of institutional strengthening in public services, and the demands for orchestration of national development programs. Therefore, this article recommends a model in which the Pandeglang Regency Government is expected to conduct a series of district institutional arrangements or restructuring in order to realize the effectiveness of district administration as a supporting force in the administration of regional government.Â